2020
DOI: 10.1007/s00394-020-02340-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary macronutrients do not differently affect postprandial vascular endothelial function in apparently healthy overweight and slightly obese men

Abstract: Purpose Well-designed trials comparing side-by-side effects of macronutrients on postprandial endothelial function are missing. Therefore, we investigated under well-controlled and isocaloric condition effects of fat, carbohydrates, and protein on postprandial endothelial function as assessed by brachial artery flow-mediated vasodilation (FMD), an important noninvasive technique to assess endothelial function. Methods Eighteen apparently healthy overweight and slightly obese men (BMI 26.0-35.0 kg/m 2) complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…In addition, differential effects of hormones, such as insulin, might play a role in explaining differences between postprandial changes in FMD as compared with longer-term effects on fasting FMD. However, in a recent study, we found that different postprandial insulin responses were not linked to differences in postprandial FMD [56]. Moreover, differences could have been caused by different effects on inflammation.…”
Section: Table 2acontrasting
confidence: 53%
“…In addition, differential effects of hormones, such as insulin, might play a role in explaining differences between postprandial changes in FMD as compared with longer-term effects on fasting FMD. However, in a recent study, we found that different postprandial insulin responses were not linked to differences in postprandial FMD [56]. Moreover, differences could have been caused by different effects on inflammation.…”
Section: Table 2acontrasting
confidence: 53%
“…Although a single high-fat meal did not significantly affect HMG-CoA reductase mRNA activity in mononuclear human blood cells during a 10-h postprandial period [24], which may suggest no effect on cholesterol synthesis, a study in obese subjects reported that HMG-CoA reductase mRNA levels were not significantly correlated with HMG-CoA reductase activity [25]. The decrease in endogenous cholesterol synthesis may also be related to postprandial changes in insulin, which increased after consumption of all three meals [18]. Previously, plasma mevalonate levels e an intermediate in the endogenous cholesterol biosynthesis pathway e have been measured during a 3-h hyperinsulinemic euglycemic clamp [26,27].…”
Section: Discussionmentioning
confidence: 97%
“…Participants, study design, and test meals Recruitment, inclusion and exclusion criteria, and the study design have already been described in detail [18]. Briefly, twenty apparently healthy overweight and slightly obese men were included in this randomized, doubleblind, crossover trial.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting serum low-density lipoprotein (LDL)-cholesterol concentrations were calculated using the Friedewald formula [ 13 ]. More details regarding the biochemical analyses can be found in our previous study [ 12 ].…”
Section: Methodsmentioning
confidence: 99%